ADAPTASI INVENTORI KERAGUAN DALAM MEMILIH KARIER DITERAPKAN PADA PESERTA DIDIK SMA NEGERI 1 BULAKAMBA BREBES - Hani, Haris Yuftika (Fokus Konseling, 2019)
For most SMA students the most influential thing in the development task is the doubt of making career decision. On the other hand, many conflicting views claim that SMA graduates will experience defeat in terms of skills from SMK students, children from weak socio-economic conditions, difficulty continuing studies due to the high cost of post SMA studies and others, causing indecision which in turn causes anxiety and future fears of their careers. The purpose of this study was to validate Career Indecision Inventory for choosing a career in SMA N 1 Bulakamba Brebes. Validity and reliability test results show that the Inventory consists of five dimensions, namely lack of career information, lack of recognition of needs, lack of self identity, indecisiveness, and external barriers. Subjects in this study amounted to 30 students of SMA. The results of statistical analysis show that career indecision Inventory is a valid and reliable instrument for measuring career indecision Inventory that will be used school counselor to help measure career indecision Inventory to students in SMA Negeri 1 Bulakamba Brebes.